The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3892/etm.2019.7311
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of resveratrol on mice with depression

Abstract: The effect and mechanism of resveratrol on depression-like behavior in mice with depression were investigated. A mouse model of depression was established by social isolation combined with chronic unpredictable stress. The mice were randomly divided into the control group, the model group, the low dose group, the medium dose group and the high dose group. The rats in the low, medium and high dose groups were intraperitoneally injected with resveratrol 10, 20 and 30 mg/kg, respectively. The control and model gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
(11 reference statements)
3
12
0
Order By: Relevance
“…In the development of depressive-like behaviors, the rat models are manifested with reduced NPY expression [17]. Academically, the expression of NPY is evidenced to decline in mice with depression [35]. Consistently, the above-mentioned study findings are as same as the previous literature to some extent.…”
Section: Discussionsupporting
confidence: 88%
“…In the development of depressive-like behaviors, the rat models are manifested with reduced NPY expression [17]. Academically, the expression of NPY is evidenced to decline in mice with depression [35]. Consistently, the above-mentioned study findings are as same as the previous literature to some extent.…”
Section: Discussionsupporting
confidence: 88%
“…Extensive studies show that monoaminergic neurotransmission involving 5-HT, NE and DA exerts major influence on brain circuits by regulating mood, reactivity to psychological stress, self-control, motivation, drive, and cognitive performance [25]. Studies also showed that the levels of DA and 5-HT decreased in the hypothalamic tissue of patients with depression [26]. Folate is necessary for proper biosynthesis of the monoamine neurotransmitters 5-HT, NE and DA [13].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol treatment enhanced neurogenesis, upregulated Sirt1, and inhibited NF-kB activation ameliorating depression-like behaviors [ 89 ]. Moreover, resveratrol was reported to be able to increase neurotransmitters dopamine and serotonin significantly in the prefrontal cortex and NPY expression in the brain suggesting to act as an antagonist for depression treatment [ 90 ].…”
Section: The Pathogenesis Of Mental Disordersmentioning
confidence: 99%